Formação de professores de matemática: um olhar sobre o estágio curricular supervisionado - Oliveira, Iracema de Miranda (2008)
The current work was targeted at how new regulations from official documents, concerning Supervised Curricular Practice, are being implemented, given the fact that college degree institutions have the freedom to operate and follow the legal instruments. To do this study, the analysis of the Supervised Curricular Practice plan for the Mathematics degree course of two private college degree institutions in the great São Paulo was chosen. We aimed at a more precise mapping of the possibilities, challenges and limits met during the implementation process. We analyzed the Pedagogical Project of both courses and did semi-structured interviews with the courses coordinators and the practice teachers. We verified that the Supervised Practice plan of both institutions shows interesting initiatives to better an activist-oriented pedagogical practice. They show a break from the understanding of practice as a model copying or technical standardization and face the possibility of undergraduate teachers fulfill, in their practices, a conscious and changing practice. However, in the teachers and coordinators reports, we noticed that these institutions still face some old problems concerning initial graduation of teachers, such as the lack of practice supervising and, consequently, some students avoid doing them. The rethinking of the traineeship intensifies, so even more the need for a greater rapprochement between the university and the school as a way to overcome these obstacles